Integrating sequence-based GWAS and comparative genomic analysis reveals conservation and species-specificity of putative functional variants influencing tail length and tail abnormalities in pigs and sheep - Xuying Zhang; Johanna Mainzer; Isabella Giambra; Tong Yin; Petra Engel; Hannah Hümmelchen; Henrik Wagner; Axel Wehrend; Christiane Egerer; Katharina Gerhards; Gerald Reiner; Sven König (PLoS ONE, 2026)
Long tails trigger tail biting in pigs and increase the risk of flystrike infections in sheep. Tail docking has been a common management practice in both species for decades, but increasingly conflicts with legal animal welfare guidelines. Sustainable solutions require breeding strategies targeting shorter tails. In consequence, the aims were to conduct whole-genome sequencing ( WGS )-based genome-wide association studies ( GWAS ) and comparative genomic analyses ( CGA ) to explore functional elements influencing tail traits. Phenotypically divergent experimental populations of pigs and sheep were established through unified selection and mating experiments. Tail traits included tail length ( TL ) measured at birth, and tail abnormalities ( TA ) assessed radiographically at 14 weeks of age. WGS-based GWAS identified a significant locus on SSC18 in pigs and suggestive loci for TL in both species, which, together with previously reported loci for TA, were further analyzed by CGA. The genomic windows of the significant locus on SSC18 in pigs and the TL GWAS locus on OAR4 in sheep were found to be conserved, harboring six common genes with predicted functional variants. These variants were jointly associated with TL ( P lm < 0.05 ) in both species in linear regression models adjusted for sex, age of the dam, body length, and body weight. In other GWAS locus windows (±1 Mb), species-specific TL candidate genes were identified in sheep ( HOXB13, MUC5B, EPB41L3, MTCL1, PIEZO2, MPPE1, and LOXHD1 ) and in pigs ( KNL1, DISP2, SPRED1, TGFB2, and HAND1 ), each harboring associated putative functional variants. For TA, sheep-specific candidates ( PGM2, LRRC66, CRACD, LOC105601916, and SH2D4B ) and pig-specific candidates ( MYOT, TMCO6, and PCDHAC2 ) were revealed using logistic regression models ( P glm < 0.05 ). GO analyses of candidate genes predicted shared biological processes between sheep and pigs, whereas pathway analyses indicated that common carbohydrate metabolism pathways, along with species-specific immune and inflammatory signaling, and pig-specific TGF-β signaling and endochondral ossification, may contribute to tail length variation and abnormalities. These findings provided deeper insights into the genetic basis of differential embryonic tail morphogenesis and perinatal tail development across species.